Intestinal epithelial-specific PTEN inactivation results in tumor formation - Byun, D.; Ahmed, N.; Nasser, S.; Shin, J.; Al-Obaidi, S.; Goel, S.; Corner, G.; Wilson, A.; Flanagan, D.; Williams, D.; Augenlicht, L.; Vincan, Elizabeth; et al. (2011)
Intestinal epithelial-specific PTEN inactivation results in tumor formation. Am J Physiol Gastrointest Liver Physiol 301: G856-G864, 2011. First published August 11, 2011; doi:10.1152/ajpgi.00178.2011.-Phosphates and tensin homolog deleted on chromosome 10 (PTEN) is a negative regulator of phosphatidylinositol 3-kinase (PI3K) signaling that is frequently inactivated in colorectal cancer through mutation, loss of heterozygosis, or epigenetic mechanisms. The aim of this study was to determine the effect of intestinal-specific PTEN inactivation on intestinal epithelial homeostasis and tumor genesis. PTEN was deleted specifically in the intestinal epithelium, by crossing PTEN Lox/Lox mice with villin Cre mice. PTEN was robustly expressed in the intestinal epithelium and maximally in the differentiated cell compartment. Targeted inactivation of PTEN in the intestinal epithelium of PTEN Lox/Lox/villin Cre mice was confirmed by genotyping, immunohistochemistry, and qPCR. While intestinal-specific PTEN deletion did not have a major effect on cell fate determination or proliferation in the small intestine, it did increase phosphorylated (p) protein kinase B (AKT) expression in the intestinal epithelium, and 19% of animals developed small intestinal adenomas and Aden carcinomas at 12 mo of age. These tumors demonstrated pAKT and nuclear ß-catenin staining, indicating simultaneous activation of the PI3K/AKT and Wnt signaling pathways. These findings demonstrate that, while PTEN inactivation alone has a minimal effect on intestinal homeostasis, it can facilitate tumor promotion upon deregulation of (3-catenin/TCF signaling, further establishing PTEN as a bona fide tumor suppressor gene in intestinal cancer. © 2011 the American Physiological Society.